Pemberian Edukasi dan Pemeriksaan HB dalam Upaya Menciptakan Remaja Puteri Bebas Anemia - Tati Karyawati; Ahmad Zakiudin; Siska Aulia; Ridho Imanulloh (Lembaga Pengembangan Kinerja Dosen, 2024)
Anemia is a health and nutrition problem in adolescents, because if adolescents experience anemia. Adolescent girls are one of the groups that are susceptible to anemia. This is because during that period they also experience menstruation, especially if adolescent girls do not have sufficient knowledge about anemia. This community service aims to increase the knowledge of adolescent girls about anemia and through providing health education about adolescent anemia and hemoglobin level checks. This community service was carried out by providing health education and hemoglobin level checks directly to 25 seventh grade female students of Nurul Huda Middle School on November 30, 2023. The results of the HB values that showed no anemia were 14 female students (56%) and the results of the HB values that showed anemia were 11 female students (44%).